Leukaemia cutis for clinicians, a literature review - Osmola, Małgorzata; Gierej, Beata; Kłosowicz, Agata; Waszczuk-Gajda, Anna; Basak, Grzegorz; W. Jędrzejczak, Wiesław; Jurczyszyn, Artur; Ziarkiewicz-Wróblewska, Bogna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Leukaemia cutis (LC) describes infiltration of the skin by leukaemia cells, resulting in clinically identifiable cutaneous lesions. LC has a wide range of clinical manifestations, which can make it difficult to distinguish LC from other skin changes. In a group of patients, LC can be the first manifestation of leukaemia, therefore skin biopsy is crucial for the diagnosis. In this mini review, we discuss various types of leukaemia most frequently represented in leukaemia cutis, in both children and adults and skin changes in multiple myeloma, focusing on the clinical presentation of LC and prognosis in patients.